Possible effects of secular resonances in Phobos and Triton - Yokoyama, T. (Elsevier B.V., 2002)
Due to the tides, the orbits of Phobos and Triton are contracting. While their semi major axes are decreasing, several possibilities of secular resonances involving node, argument of the pericenter and mean motion of the Sun will take place. In the case of Mars, if the obliquity (epsilon), during the passage through some resonances, is not so small, very significant variations of the inclination will appear. In one case, capture is almost certain provided that epsilon greater than or equal to 20degrees. For Triton there are also similar situations, but capture seems to be not possible, mainly because in S-1 state, Triton's orbit is sufficiently inclined (far) with respect to the Neptune's equator. Following Chyba et al. (Astron. Astrophys. 219 (1989) 123), a simplified equation that gives the evolution of the inclination versus the semi major axis, is derived. The time needed for Triton crash onto Neptune is longer than that one obtained by these authors, but the main difference is due to the new data used here. In general, even in the case of non-capture passages, some significant jumps in inclination and in eccentricities are possible. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: Phobos; Triton; satellite dynamics; tides; orbital evolution; celestial mechanics